RISK ASSESSMENT FOR WORKERS’ HEALTH IN MINING PRODUCTION BASED ON THE CLUSTER ANALYSIS OF LABOUR CONDITIONS - Страшникова, Татьяна Николаевна; Олещенко, Анатолий Михайлович; Суржиков, Дмитрий Вячеславович; Кислицына, Вера Викторовна (Medicine in Kuzbass, 2017)
Subject. Labour conditions in the workers of main production and professional groups of the mining enterprise. Objective. To evaluate the hygienic labour conditions of the workers of the main production and professional groups of the mining enterprise, to calculate the risks for forming occupationally-caused pathology. Methods. A dendrite of production and professional mining groups was built based on the values of the factors of the production environment. Main results. High levels of the risk of occupationally-caused pathology were revealed when exposed to suspended particles in the air of the working area. The risk of chronic intoxication related to the gassed air in the working area with toxic compounds exceeds the acceptable level in the professional groups of mining production in 1.45-9.25 times. The main contribution to the formation of the risk of chronic intoxication is made by nitrogen oxides. The cumulative level of the risk associated with the adverse factors in the production environment is noted in the professional group of the operators of vibration loading machines. Conclusions. The application of the cluster analysis makes it possible to assess the labour conditions of the workers in industrial enterprises.